Features of the course of COVID-19 in children undergoing outpatient treatment - A. L. Bondarenko (Детские инфекции (Москва))
Objective: to study the clinical and epidemiological features of the course of a new coronavirus infection in children of different ages undergoing outpatient treatment.The study participants were 812 children with COVID-19 aged from 1 month to 17 years, who were on outpatient treatment in the children's polyclinic of the city of Kirov from July to December 2021. The average age of patients with COVID-19 was 5.9 ± 1.1 years. Among the sick young children there were 28%, adolescents — 16%. In 76% of cases, contact with patients with a new coronavirus infection was detected, mainly in the family, as well as in educational institutions. In 70% of cases, an early request for medical help was registered — in the first three days of illness. In most cases (89%), a mild severity of the disease was established with the development of subfebrile fever and pharyngitis. Rhinitis phenomena were recorded in 20% of cases. 7% of children complained of a dry cough. Lung tissue lesion (RG1) was detected in 5% of patients, gastrointestinal tract — 5%. In adolescents, the phenomena of rhinitis, pharyngitis, dry cough were less common than in other age groups. Recombinant interferon alpha-2b and umifenovir were used for etiotropic therapy. All children recovered within 7—10 days from the onset of the disease.